2014
DOI: 10.1016/j.celrep.2014.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of mTORC1 Signaling Recapitulates Microcephaly, Tuberous Sclerosis, and Neurodegenerative Diseases

Abstract: Mammalian target of rapamycin (mTOR) has been implicated in human neurological diseases such as tuberous sclerosis complex (TSC), neurodegeneration, and autism. However, little is known about when and how mTOR is involved in the pathogenesis of these diseases, due to a lack of animal models that directly increase mTOR activity. Here, we generated transgenic mice expressing a gain-of-function mutant of mTOR in the forebrain in a temporally controlled manner. Selective activation of mTORC1 in embryonic stages in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 46 publications
4
72
0
1
Order By: Relevance
“…S7 B-D). This result is in agreement with a previous study that also found that S6K1/2 knockdown was not sufficient to block mTORC1-induced neuronal misplacement (6).…”
Section: Significancesupporting
confidence: 83%
See 2 more Smart Citations
“…S7 B-D). This result is in agreement with a previous study that also found that S6K1/2 knockdown was not sufficient to block mTORC1-induced neuronal misplacement (6).…”
Section: Significancesupporting
confidence: 83%
“…S3). Finally, we examined soma size because increased mTORC1 activity causes cellular hypertrophy (6,(21)(22)(23). As expected, a 2.1-fold increase in soma area was observed in Rheb CA -electroporated cells relative to controls (Fig.…”
Section: Significancementioning
confidence: 86%
See 1 more Smart Citation
“…These findings provide evidence why some patients with ASD who have gene mutations in one negative regulatory protein of mTOR, the phosphatase and tensin homolog (63,64), develop inflammation of the brain that is linked to ASD pathogenesis (65,66).…”
Section: Discussionmentioning
confidence: 88%
“…Transgenic overexpression of mTOR in murine brains culminates in cortical atrophy and neurodegeneration (Kassai, Sugaya, Noda, Nakao, & Maeda, 2014), while conditional knockout of Tsc1 (TSC complex subunit 1), an mTOR inhibitor, has also successfully induced the neurodegenerative abnormalities in mouse brains, a phenocopy of AD pathophysiology (Carson, Nielen, Winzenburger, & Ess, 2012) (Table 2). At present, activation of mTOR has been recognized as a major event that causes AD pathogenesis (Yates, Zafar, Hubbard, Nagy, & Durant, 2013).…”
Section: The Important Role Of Protein Synthesis Pathways In Cancer Amentioning
confidence: 99%